The Effect of Good Corporate Governance on Corporate Social Responsibility on Company Value With Profitability as an Intervening Variable (Empirical Study on Consumer Goods Sector Companies Listed on the Indonesia Stock Exchange for the 2019-2023 Period) - Risa Bonani Prastika; Rusdi Hidayat Nugroho; Budi Prabowo; Indah Respati Kusumasari (Universitas KH. Abdul Chalim Mojokerto, 2025)
With profitability serving as a mediator, this research seeks to examine the impact of Good Corporate Governance and Corporate Social Responsibility on business value. Managerial ownership, institutional ownership, and independent commissioners are the proxies of good corporate governance. The GRI is what's known as